2022
DOI: 10.3390/nu14091694
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Oil Reduces Aβ Levels and Increases Neurite Length in a Cellular Model of Early Alzheimer Disease

Abstract: (1) Background: Mitochondria are the cells’ main source of energy. Mitochondrial dysfunction represents a key hallmark of aging and is linked to the development of Alzheimer’s disease (AD). Maintaining mitochondrial function might contribute to healthy aging and the prevention of AD. The Mediterranean diet, including walnuts, seems to prevent age-related neurodegeneration. Walnuts are a rich source of α-linolenic acid (ALA), an essential n3-fatty acid and the precursor for n3-long-chain polyunsaturated fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…21,22 In addition, some studies have found that linolenic acid also played a positive role in protecting mitochondrial function, such as regulating mitochondrial biology and mitochondrial dynamics, restoring mitochondrial quality control to improve mitochondrial dysfunction and structural damage. 23–27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In addition, some studies have found that linolenic acid also played a positive role in protecting mitochondrial function, such as regulating mitochondrial biology and mitochondrial dynamics, restoring mitochondrial quality control to improve mitochondrial dysfunction and structural damage. 23–27…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In addition, some studies have found that linolenic acid also played a positive role in protecting mitochondrial function, such as regulating mitochondrial biology and mitochondrial dynamics, restoring mitochondrial quality control to improve mitochondrial dysfunction and structural damage. [23][24][25][26][27] Based on previous studies, the hypothesis of this study was that the amelioration of sarcopenia by linolenic acid is related to mitochondrial function and oxidative stress. C. elegans is a model animal for screening bioactive components due to its simple feeding, short growth cycle and rapid reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…The water extract of walnut ( Juglandis semen ) has exhibited pivotal neuroprotective action in various research studies. This extract was found to deplete ROS and NO (nitric oxide) growth, further blocking the loss of DA, thus showing exceptional recovery in patients with PD ( Esselun et al, 2022 ). In another investigation by Yang et al, the walnut-derived polypeptide (TW-7) observed antioxidant action simultaneously initiating autophagy.…”
Section: Phytoconstituents In Different Neurological Disordersmentioning
confidence: 99%
“…In addition, polyphenols have protective effects on blood vessels and the heart and can prevent thrombosis [ 122 ]. Anti-cancer and neuroprotective effects have also been described [ 123 , 124 , 125 ] ( Table 1 ).…”
Section: Polyphenols and Secondary Plant Metabolites In Aging Researchmentioning
confidence: 99%